Coronavirus disease 2019 in neonates - Linardi, Jade Irene (International Journal of Contemporary Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19) as a global pandemic has become a major burden especially in the health care system and economy. COVID-19 has clinical presentations ranging from remain asymptomatic to severe acute respiratory distress syndrome (ARDS) and death. All age groups are susceptible to this virus, but it seems that children with COVID-19 have milder symptoms than adults. Neonates, however, have been reported to have more severe cases compared to older children. There is also a possibility of vertical transmission from mothers to their neonates which could not be ignored. This review provides current knowledge of COVID-19 in neonates.